Clinical, endoscopic and histologic evaluation of gastroesophageal reflux disease in patients treated with proton pump inhibitor: a prospective study - Hossain, Mir Jakib; Nuruzzaman, Md; Islam, Md Rafiqul; Hasan, Md Nazmul; Islam, Menhazul; Raihan, ASMA (Bangladesh Medical Journal, 2016)
This study was done to demonstrate the histological changes in gastroesophageal reflux disease (GERD) before and after proton pump inhibitor (PPI) therapy as well as, to evaluate the efficacy of PPI in patients with GERD and to find out the healing rate of erosion in erosive reflux disease after PPI therapy. This hospital based prospective study was conducted among 57 patients suffering from gastroesophageal reflux disease who were recruited from the outpatient department of gastroenterology of Bangabandhu Sheikh Mujib Medical University. It was carried out from May 2008 to December 2008. Most of the GERD patients had non erosive disease (63.2% vs 36.8%). PPI was effective to relieve the major symptoms of GERD. In erosive group (n=21), at the end of 28th day, heartburn was present in 3(14.3%) patients. In non-erosive group (n=36), at the end of 28th day heartburn was present in 6(16.7%) patients. Changes in histological parameters were also found to be significant before and after therapy. GERD patients had characteristic histologic changes in lower esophagus and after 4 weeks of treatment with PPI, there was significant improvement of symptoms, endoscopic and histological features of reflux disease. Bangladesh Med J. 2015 Sep; 44 (3): 121-124